Some comments on the teaching of stochastic processes to engineers. (4th August 2014) - Cox, David R.; Davison, Anthony C.
The contribution of stochastic processes in modelling dynamic phenomenena is reviewed. The key ideas are identified, the importance of careful formulation is emphasised and the roles of analytical solution and simulation discussed. A simple example is investigated in a little detail.